The Influence of Organizational Commitment and Job Satisfaction on Organizational Citizenship Behavior (OCB) of Civil Servants at the Sanggau Public Works and Water Resources Department - Ahmad Zulkhairin; Arnida (Jurnal Manajemen Bisnis, 2025)
Quantitative research with an associative/relationship approach. The number of samples is 47 employees. The data collection method uses questionnaires and interviews. Data analysis using instrument test, classical assumption analysis, multiple linear regression analysis, correlation coefficient (R), determination coefficient (R2), simultaneous influence test (F test), and partial influence test (t test). Result: Based on the results of multiple linear regression analysis, the regression equation is Y = 1.779 + 0.365X1 + 0.316X2. The correlation coefficient (R) of 0.683, indicates that the relationship between organizational commitment variables (X1) and job satisfaction (X2) on organizational citizenship behavior (OCB) (Y) is strong. The determination coefficient (R2) of 0.467, which means that the contribution of organizational commitment variables (X1) and job satisfaction (X2) to organizational citizenship behavior (OCB) (Y) is 46.70%. The t influence test shows that Organizational Commitment individually has an influence on Organizational Citizenship Behavior (OCB) on employees of the Sanggau Highways and Water Resources Service. Individual job satisfaction has an influence on Organizational Citizenship Behavior (OCB) in Sanggau Highways and Water Resources Department employees. There is an influence on Organizational Citizenship Behavior (OCB) in employees of the Sanggau Highways and Water Resources Service.